Globalization and developing countries - a shrinking tax base? - Joshua Aizenman; Yothin Jinjarak (University of California, Economics Department, 2006)
This paper evaluates the impact of globalization on tax bases of countries at varying stages of development. We see globalization as a process that induces countries to embrace greater trade and financial integration. This in turn should shift their tax revenue from easy to collect taxes (tariffs and seigniorage) towards hard to collect taxes (value added and income taxes). We find that trade and financial openness have a positive association with the hard to collect taxes, and a negative association with the easy to collect taxes.
Keywords: F15; H21; 330; Globalization; tax base; fiscal convergence; VAT; financial repression; tariff; Globalisierung; Steueraufkommen; Steuerbemessung; Indirekte Steuer; Direkte Steuer; Vergleich; Entwicklungsländer